Factors affecting credit risk in India microfinance institutions - Boon, Jun Yu; Chia, Yi Jing; Tan, Angel; Tan, Xiu Wei; Yong, Wai Yan (2023)
The purpose of this research is to determine the factors that affect the credit risk of microfinance institutions in India. Quantitative research methods had been applied in this study by using the data that was obtained from the World Bank as well as the annual report from the six major microfinance institutions in India. E-views had been used for analyzing the data with descriptive analysis, Diagnostics test, F-statistic, T-statistic, Poolability test and Breusch and Pagan Lagrange Multiplier (BPLM) test. The results found from E-views indicates that independent variables which are Loan Size (LS) and Household Income (HI) are significantly affect the credit risk of microfinance institutions in India while the other three independent variables which are Gross domestic product growth (GDP growth), Capital Adequacy Ratio (CAR) and Real Interest Rate (RIR) are insignificantly affect the credit risk of microfinance institutions in India. Furthermore, this study provided benefit to the India government to provide guidance and reference for policy implication.